Supervisi Akademik Kepala Sekolah Dalam Meningkatkan Kualitas Pembelajaran Guru - Maulana, Arya Dian; Sayan Suryana (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
Supervision of principals in fostering the quality of teacher learning is one of the important programs that must be implemented by principals in fostering teachers to improve the quality of learning. The purpose of this research is to find out the steps taken by the principal in improving the quality of learning supervision, through this research can get fresh air for the principal in improving the quality of learning through supervision of teachers. With the quality of teacher, learning will have a positive impact on in order to improve the quality of education. However, the problem is that the supervision carried out by the principal is still not optimal, this will not have a good impact on improving the quality of education. So the target is the teacher in the learning process, which consists of the main material in the learning process, the compiler of the syllabus and lesson plans, the selection of learning strategies/methods/techniques, the use of media and information technology in learning, assessing the learning process and results as well as classroom action research. Academics in every school are needed to improve the quality of learning.